Nature of the beast: in Uganda, people and primates face unique struggles - Rolston, Holmes, 1932-2025, author; Fort Collins Coloradoan, publisher (Colorado State University. Libraries, 2003)
Report on trip to Uganda: gorilla and chimpanzee conservation and development. Uganda primate encounters leave a more lasting searching both for human origins and future hopes. Here the human species, exemplified in these Ugandans overcoming tragedy and hardship, is seeking to conserve these nearest of our primate kin. Paradoxically, in that very caring, we reveal the still quite stupendous divide that separates us from them.
Keywords: endangered species; conservation; chimpanzee; gorillas; Uganda